ANALISIS RANCANGAN PEMBELAJARAN TEMATIK GURU DI KELAS V SEKOLAH DASAR NEGERI 66 PONTIANAK KOTA - Rita Ermia; Tahmid Sabri; Dyoty Auliya Ghasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study aims to describe the suitability of the contents of each component in the class V thematic learning implementation plan at 66 Pontianak City Elementary Schools referring to the Regulation of the Minister of Education and Culture Number 22 of 2016 concerning Process Standards. The research method used is descriptive qualitative method with the form of case study research. Data collection techniques used in this research are indirect observation techniques, interview techniques, and documentary studies. The data collection instrument in this study was the researcher himself as the main instrument using observation guidelines, interview guidelines, and teacher lesson plans documents on theme 2, sub-theme 1 learning 1, learning 2, learning 3, learning 4, learning 5, and learning 6. Based on the data The results of observations, interviews, and RPP documents showed that the results of the analysis were that there were several components that were suitable and there were also some that were not suitable which needed to be improved a lot in making the lesson plans. Keywords: Components, Learning Implementation Plan, Regulation of the Minister of Education and Culture